Plant regeneration from axillary bud, callus and somatic embryo in carnation (Dianthus caryophyllus) and assessment of genetic fidelity using RAPD-PCR analysis - KUMAR, SURINDER; KUMARI, RAJNI; BAHETI, TRIPTI; THAKUR, MANISHA; GHANI, MINERVA (The Indian Journal of Agricultural Sciences, 2016)
Plant regeneration was achieved from axillary bud, callus and somatic embryos of Dianthus caryophyllus cv.Yellow Dot Com from node and leaf explants cultured on Murashige and Skoog (MS) medium supplemented with plant growth regulators. The explant nodal cutting responded well for direct regeneration while leaf explant was selected for callus induction. The highest number of direct adventitious shoots were achieved with 9.08 μM TDZ and 5.37 μM NAA. The maximum callus induction was achieved with 2.06 μM 2, 4-D and 2.68 μM NAA. The calli derived from MS medium supplemented with 5.37 μM NAA and 2.27 μM TDZ were found to have maximum shoot regeneration potential. The highest number of calli producing shoots and average number of shoots per callus was recorded on MS medium supplemented with 9.12 μM zeatin and 5.07 μM IAA. The calli derived from leaf explants cultured on medium containing 2.06 μM 2, 4-D and 2.68 μM NAA were highly friable, had poor regeneration potential and were selected for cell suspension studies. The cultures were allowed to grow into micro-colonies in liquid medium and subsequently into embryogenic calli on semi-solid and solid MS medium which later differentiated into somatic embryos without growth regulators. Plantlets were obtained from in vitro derived shoots/somatic embryos with 60-80% survival after 30 day of transfer to pots. The plants regenerated from axillary buds, callus and somatic embryos were compared with mother plant to assess genetic fidelity using RAPD and 2.94%, 26.47% and 20.58% variation was observed, respectively.